Kadar klorofil ekstrak daun pepaya pada jenis pelarut dan kadar zat penstabil yang berbeda - Poppy Diana Sari; Lukman Hudi; Al - Machfud; Aisyah Nurkhaliza; Erika Puspita Sari (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Chlorophyll is a green coloring agent and antioxidant from plants that is needed in everyday life, both in the food industry, cosmetics and renewable energy. Its abundant presence in nature makes it interesting to research and develop its use. Various methods are used to extract chlorophyll from existing natural materials. One type of plant with the highest chlorophyll content is papaya leaves, but the highest chlorophyll content has not been found from the extraction process used so far. The use of papaya leaves has only been used for animal feed so it is very interesting to develop in order to be used further in other things. This study aims to obtain the highest chlorophyll content with the treatment of solvent types and levels of stabilizers used in the papaya leaf chlorophyll extraction process. The study was conducted with 2 treatment variables, including the type of solvent, namely ethanol and seton and the treatment of the levels of NaHCO3 stabilizers used, namely 1%, 3% and 5%. From the research that has been done, the highest results were obtained in the treatment using acetone as a solvent and the addition of NaHCO3 stabilizer as much as 3%. This treatment resulted in an extract yield of 7.56%, an average total chlorophyll content of 10.597%, an average chlorophyll a content of 5.916% and an average chlorophyll b content of 4.684%.